Assessment of The Impact of Use of Electronic Gadgets On Sleep Pattern and Daytime Sleepiness Among Nonobese Students in A Selected College At Puducherry, India - A Cross-Sectional Observational Trial.: Life Sciences-Nursing - P, Sumathy (International Journal of Life Science and Pharma Research, 2023)
Humans suffer from various sleep disorders because of using electronic gadgets, especially adolescent college students. Frequent and additional prolonged use of electronic gadgets before bedtime may lead to daytime sleepiness and other sleep disorders such as insomnia, hypersomnia, sleep apnea, etc., The study aimed to assess the impact of electronic gadgets on sleep patterns and daytime sleepiness among adolescents with a normal BMI in a selected college in Puducherry. A quantitative research approach and a descriptive cross-sectional research design were adopted for the study. Adolescents in the age group of 16-19 years of each gender were the target population. A total of 298 adolescents participated in the study. The tool consisted of socio-demographic variables, a sleep habits questionnaire to assess the sleeping pattern, and a modified Cleveland adolescent sleepiness questionnaire to evaluate the adolescent experience of daytime sleepiness on a 5-point Likert scale. The results indicate that smartphones and television were the most commonly used electronic gadgets among adolescents. Most adolescents went to bed after 10 pm and woke up after 6 am. The majority of the adolescents felt somewhat sleepy during the daytime. An association existed between the use of smartphones and laptops with daytime sleepiness at p<0.05: Electronic gadgets have become a part of adolescents’ life, and it has an impact on the adolescents’ sleep habits which needs to be addressed earlier.